Validitas Logis Model Pembelajaran Eskalasi untuk Pembelajaran Fisika di SMA - Sugiono Sugiono; Sudarti Sudarti; Sutarto Sutarto (Program Studi Magister Pendidikan IPA FKIP Universitas Jember Bekerjasama dengan Perkumpulan Pendidik IPA Indonesia (PPII), 2016)
The core of learning science are two concepts: process and product. The process is a learning-based scientific approach. Studies have shown that the implementation of a scientific approach for learning physics in high school is not running well. Therefore, we need to develop the Eskalasi Learning Model (ELM) based scientific approach. The model of learning can be categorized as valid if the expert, user, and audience agree. The aim of the research is to analyze the validity of the ELM by the expert validators. The expert validators are three lecturers in science teaching. The expert validators will assess the validation instrument, which consists of characteristics of the model and learning tools. The final score is the average of three expert assessments, and it will be matched by the categories. Based on validation by experts, we can conclude that the characteristics of the ELM (rational models, supporting theory, syntactic, social system, the principle of the reaction, the supporting system, the instructional and nurturant effect) and learning tools are valid and can be implemented to physics learning in high school.